Pengaruh Independensi, Kompetensi Dan Tekanan Waktu Terhadap Kualitas Audit: Studi Kasus Pada Kantor Akuntan Publik Di Wilayah Surabaya - Rida Ayu Pratiwi; Syaiful Syaiful (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Examining the potential relationship between audit quality and factors like independence, competence, and time pressure is the primary goal of this study. Auditors from Surabaya-area Public Accounting Firms (KAP) make up the sample population used in this study. There were a total of 51 respondents selected using a purposive selection technique. Descriptive statistics, validity, and reliability tests were performed on the data before analysis. Following this, do the traditional set of tests for assumptions, which includes the tests for normality, multicollinearity, and heteroskedasticity. Multiple linear regression analysis is used in this study. Coefficient of determination (R2), partial test (t test), and simultaneous test (F test) are the outcomes of hypothesis testing. This study's hypothesis testing findings reveal that while time pressure does not affect audit quality, independence and competence do. Limitations of this study include the fact that the questionnaire was only distributed in the Surabaya region.